Water permeability of Eco-Friendly Ductile Cementitious Composites (EDCC) under an applied compressive stress. (March 2020) - Wang, Qiannan; Banthia, Nemkumar; Sun, Wei; Gu, Chunping
Abstract: Permeability of concrete is one of its most important characteristics determining the durability. In this study, water permeability of a new class of fiber reinforced concrete materials called Eco-Friendly Ductile Cementitious Composites (EDCC) was studied, with and without an applied compressive stress. Hollow-core specimens were used and permeability tests were performed under full flow-equilibrium conditions. Four applied stress levels of 0.3 f u, 0.4 f u, 0.5 f u and 0.6 f u were investigated, where f u is the compressive strength of the EDCC in question. Permeability tests under identical conditions were carried out on plain control specimens without fiber reinforcement (termed Plain Cementitious Composites, PCC). The results indicated that the permeability of unstressed specimens declined over time due to the continuous hydration. A 'critical' compressive stress level ( f cc ) was identified and defined, which when exceeded, a dramatic increase in the coefficient of permeability occurred. The 'critical' compressive stress level ( f cc ) was noted to be between 0.5 f u 0.6 f u for EDCC and 0.4 f u 0.5 f u for PCC. In other words, EDCC was more damage tolerant than PCC, and even when f cc was exceeded, the impact of stress on the permeability of EDCC was far less pronounced compared to PCC.